ANALYZING COVID-19 DYNAMICS IN TWO NON-INTERACTING REGIONS THROUGH A STRUCTURED COMPARTMENTAL MODEL - Muhammad Afief Balya; Dipo Aldila; Yuni Yulida; Sila Rizqina; Pardi Affandi (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2025)
COVID-19 is an infectious disease caused by the corona virus. Corona Virus or Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. This paper will discuss the effect of the absence of human mobility on the spread of COVID-19. The proposed model consists of ten compartments, including susceptible, exposed, infected (symptomatic and asymptomatic), and recovered individuals in both regions. The model construction in this paper is quite simple, namely it does not involve human mobility at all. This is important because by understanding the characteristics of COVID-19 in a closed population, the spread of COVID-19 locally can be anticipated. Both analytical and numerical approaches are used. The numerical study involves elasticity analysis to identify key influential parameters and autonomous simulations to observe the long-term behavior of the system.